The translation of conceptual metaphor in political news - Siriam, Siriam; Widyastuti, Susana (Diksi, 2023)
Metaphorical expressions (MEs) are abundant in political text and their translation "Žposes challenges particularly for retaining the implicit meaning. This research focuses on examining the use of conceptual metaphors (CMs) "Žin Indonesian "Žpolitical news and their English translation. The objectives "Ž are to identify types and the source domain of CMs and to explain how the CMs are translated."Ž "ŽGrounding on mixed-methods, the data were metaphorical expressions in "Ž the Indonesian and English versions of Tempo weekly magazines in April, May, and June in 2021. Metaphor Identification Procedure  (MIP) was "Žapplied to determine the metaphoricity of metaphors in the STs and Indonesian dictionary (KBBI) was also employed to avoid intuition "Ždecision-making. "ŽThe results indicate that CMs are commonly used in "Žpolitical news in order to popularize, concretize, and dramatize issues. Structural metaphors are found "Žas the most dominant type and twenty source domains are found "Žin the STs with war metaphor as the most significant domain. In terms of the translation, the study demonstrates that non "Žmetaphorical translation is the most frequently used technique to render metaphors "Žinto English TT. As a result, the translation reduces the "Žmetaphoric function of the original expressions.Keywords: political news, conceptual metaphor, translation technique